PENGARUH UMPAN TERHADAP HASIL TANGKAPAN ALAT TANGKAP ANCO (LIFT NET) DI PERAIRAN RAWA BULUNG KULON, KABUPATEN KUDUS - Hermanto, Alfian; Wibowo, Pramono; -, Asriyanto (Journal of Fisheries Resources Utilization Management and Technology, 2012)
Anco is a very simple lift net, generally used only by small fishermans. The shape of the tool is rectangular. The shape is used because after setting and hanging, the other side of the net look like a cup. Anco is used on the edge of the river and the swamp, especially in the estuarine water stream. On that section, there are many small fish schooling because the fish like to swim on the opposing direction of the water stream. Bait is used as stimulant for the fish, so that the fish schools around the anco net. The purpose of this reseatch is to analyze the use of shrimp’s natural bait, worm and cassava against the anco net catch result and to know what bait that has the biggest influence against the anco net catch result. The research method used is descriptive, this research is an experimental research to test modified bait from many kinds of bait (mashed worms, mashed shrimp, mashed cassava) against the catching result in the use of anco net to catch fish. Direct observation method, interview, documentation, and literature is used to collect data. Data is then analyzed using statistic test including testing the normality, testing the homogenity, and one way Anova testing. The results of three treatmens used in the research are shrimp bait, worm, and cassava. The bait which has the most catching result in terms of result, 928 fishes and weighing 3,193 kg, but, the most catching result in the terms of weight is the shrimp bait, weighing 6,466 kg, 840 fishes. The worm bait resulting in 758 fishes, weighing 5,285 kg.